Level of Risk Awareness and Insurance Literacy of Ilocanos Residing in Ilocos Sur - Nalchael T. Cruz; Leslie De Castro; Divina Daniel A.; Jana Mae S. Rapada; Joy Melanie N. Rebuldela (Research Synergy Foundation, 2024)
Numerous individuals exhibit hesitancy towards procuring insurance, potentially attributed to their confidence in not requiring it or their perception of insurance as excessively complex, influenced by the plethora of available information. The objective of this study was to determine the level of risk awareness and insurance literacy of the general public in different municipalities and component cities of Ilocos Sur. There were five hundred thirty-four (534) individuals from different municipalities in Ilocos Sur, and stratified random sampling was used. This study employed a descriptive-correlational research design using a quantitative approach. The researchers used a survey questionnaire as the primary research instrument. To correlate the levels of awareness of the Ilocanos about health and life insurance with their insurance literacy, the researchers used the International Business Machine Statistical Package for the Social Sciences (IBM SPSS), specifically correlation analysis. The research shows a strong correlation between risk awareness and insurance literacy among the general public in Ilocos Sur, with respondents exhibiting heightened awareness of safety, security, return, and liquidity aspects of insurance, emphasizing health as a primary concern, and placing significance on familial considerations when insurance. The data indicates a clear understanding of the concept of beneficiaries and reflects a discerning public with a keen understanding of insurance decisions.